The impact of dynamic learning program using the SRA reading materials on the reading proficiency of the university of Iloilo-PEN college freshmen - Labiste, Jessie L (University of the Philippines Visayas, 2014)
This study evaluates the initial implementation of the Dynamic Learning Program using the SRA Reading Laboratory in Eng 104 classes of University of Iloilo-PEN. The study utilized 354 student-respondents enrolled in ENG 104 classes and 8 teacher-respondents who handled the subject during the first semester of school year 2013-2014. The reading levels, before and after taking ENG 104, were compared. A researcher-made instrument was used to determine the perception of students and teachers in using DLP in ENG 104 classes. Results revealed that the reading proficiency of the students significantly improved while the respondents find the use of DLP helpful in improving reading proficiency. Further suggestions in improving the use of DLP in ENG 104 classes are discussed.